EVALUASI KUALITAS MAJALAH DINDING BERBASIS KOMPUTER PADA MATA KULIAH PUBLIKASI MODE - Mentari Pertiwi; Winwin Wiana (Fesyen Perspektif, 2015)
Evaluate the quality of the wall  magazine conducted for measure the capabilities and  assess the quality of the resulting  product  to increase an interesting visualization. This research aims to obtain  data on the quality evaluation result based assement  wall  magazine of  theme, rubric, article content, can  apply  the element and  principal of  layout, and  the ability to operate the software . In this research benefit to be expected to improve the  quality of  assessment in order to improve the quality and standar wall magazine  for a better future. The method used  is descriptive analytic with a total sample by collecting the data through article archive documentation based on the assignment of  creating wall  magazine which consisted of 30 documentation articles as the samples which are related to the Fashion Publication assignment for the students of Design Management,  Fashion Education Major of UPI batch 2010 and 2011. According to the result of the study, it can be concluded  that largely of the students can create an interesting layout for wall magazine based on the quality assessment that interprets the theme  and  rubric. Reviewed , based on the quality assessment of managing the text element, the study result showed that more than half of the students involved in this study can apply the  Headline, subhead, initial caps, bodytext, byline dan wordart, on the layout .Reviewed , based on the quality assessment of managing the visual element, the study showed that more than half of the students involved in this study can apply the Artworks,ornament, background, dan line, Then based on the quality assessment of managing the invisible element, the study showed  that a  half of  the students involved in this study can apply the margin, grid, dan column.Then based on the quality assessment of layout arrangment principal, the study showed that largely of the majority of the respondents have the capability of presenting the quality of sequence, emphasis, balance and unity application, Then the last one was based on the quality assessment to operate software, the study showed that largely of the respondents have the capability of operate software, over all these data are excellent qualifications.